The Application of Anthony Giddens' Structuration Theory to Rumeksa Dance in Banyumas District - Purwaningtyas, Indah Sukma; Sutiyono, Sutiyono; Bagaskara, Akbar (International journal of multicultural and multireligious understanding, 2023)
This study aims to describe the results of the analysis of the Implementation of Anthony Giddens' Structuration theory in Rumeksa Dance in Banyumas Regency.This research uses descriptive qualitative method. The object of research is Rumeksa Dance in Banyumas Regency. The research subjects were DINPORABUDPAR staff and Rumeksa dance choreographers. Data collection techniques by means of observation, in-depth interviews, and documentation. Test the validity of the data using the technique triangulation method.The results showed that: (1) Rumeksa dance is divided into 3 scenes, namely Lenggeran, Baladewa or Kiprahan, and Ebeg. (2) Rumeksa Dance was initiated by Mr. Mardjoko, the choreography used adapted from Lengger Dance with the aim that future generations can learn Lengger dance with a shorter duration. (3) in Anthony Giddens' Structuration Theory, the agent or person who plays a role in creating differences is Mr. Mardjoko. While the agency or event that the agent is responsible for is Rumeksa dance.